The influence of hydrostatic pressure on the interlaminar fracture toughness of carbon/epoxy composites - Cartié, Denis D. R.; Davies, P.; Peleau, M.; Partridge, Ivana K. (Elsevier Science B.V., Amsterdam., 2006)
The use of composites for deep sea applications requires a thorough understanding of the behaviour of these materials. While several studies have examined the influence of pressure on in-plane properties few data are available for the interlaminar fracture behaviour. This paper presents results from such tests performed in a specially designed pressure vessel mounted on a standard test machine, which allows pressures up to 1000 bars (100 MPa) to be applied during mechanical testing. Mode I and Mode II tests have been performed on a unidirectional IM7/977-2 carbon/epoxy composite. No effect of pressure was noted on Mode I fracture toughness. A data reduction scheme has been developed for Mode II loading and an increase in GIIC with increasing pressure was noted.